Legal Review of Dangerous Skincare Users in the Perspective of Islamic Law and Consumer Protection Law - Rahmadi Indra Tektona; Ayu Citra Santyaningtyas; Emi Zulaikha (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Skin beauty is a primary need for women, and it caused the cosmetic market to increase significantly for domestic and foreign brands throughout the year. There has been abuse by irresponsible entrepreneurs by selling and producing skin care products that do not meet Indonesian Food and Drug Authority (BPOM) requirements. The focus of this review is to find out how the legal review of dangerous skincare users in the perspective of Islamic law and consumer protection act (Law of the Republic of Indonesia Number 8 Year 1999 concerning Consumer Protection). The research method used in this study is normative juridical research with statutory and conceptual approach. The results of the study show that Islam provides more protection for women and there are internal and external legal protections in Indonesia for skincare users.